About Amoroso Costa: a conversation with Arthur Gerhardt Santos - Fabris, Júlio; Guimarães, Luiz Filipe de Oliveira (Cadernos de Astronomia, 2024)
Amoroso Costa was a Brazilian mathematician, who tragically died in December 1928 in a plane crash, when they were planning a tribute to Santos Dumont upon his return to Brazil.He dedicated himself to studies on General Relativity, non-Euclidean Geometries, Theories of Numbers, and fought positivism, a predominant doctrine in Republican Brazil at the beginning of the 20th century. Arthur Gerhardt Santos, governor of Espírito Santo in the early 1970s, dedicated himself to studying the life and work of this important pioneer of Science in Brazil. This text reproduces a conversation with Gerhardt Santos about Amoroso Costa. It was an opportunity to talk about several other parallel issues such as positivism, science and education in Brazil.
Keywords: Amoroso Costa; general relativity; non-Euclidean geometries; positivism